Existential meaning, burnout and cultural differences among universities staff - Abdul Razak, Abdul Latif (s.n, 2012)
This cross-cultural study is an attempt to examine the relationship between meaning and burnout among university staff in Malaysia and Thailand using the Life Regard index and the Copenhagen Burnout Inventory (English version)